2016
DOI: 10.1016/j.ncl.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Manifestations of Human Immunodeficiency Virus/AIDS

Abstract: Synopsis Behavioral disorders are common in HIV-infected (HIV+) persons. The differential includes pre-existing psychiatric diseases, substance abuse, direct effects of HIV infection, opportunistic infection (OI), and the adverse effects of medical therapies. Many patients have more than one contributing or co-morbid problem to explain these behavioral changes. The differential should always include consideration of psychosocial, genetic, and medical causes of disease. Treatment strategies must take into accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 134 publications
0
26
0
Order By: Relevance
“…Moreover, the existing evidence showed that HIV-positive status is directly linked with mental disorders via neuro-biological mechanisms [ 54 ]. HIV-positive status is also indirectly related to mental disorders through stigma and discrimination [ 55 ], particularly among people living with HIV without access to antiretroviral therapy (ART) and insufficient or late ART receipt [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the existing evidence showed that HIV-positive status is directly linked with mental disorders via neuro-biological mechanisms [ 54 ]. HIV-positive status is also indirectly related to mental disorders through stigma and discrimination [ 55 ], particularly among people living with HIV without access to antiretroviral therapy (ART) and insufficient or late ART receipt [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This adjustment difficulty—presenting as psychological distress—may occur after receiving HIV positive diagnosis; when HIV symptoms begin to develop; at the start of lifelong antiretroviral medication and also in terminal care. 24 Second, the direct effects of HIV virus on the central nervous system 25 may lead to behavioural changes resulting into symptoms of depression. Third, such psychological disturbance may also be because of HIV-related stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing evidence showed that HIV-positive status is directly linked with mental disorders via neuro-biological mechanisms [54]. HIV-positive status is also indirectly related to mental disorders through stigma and discrimination [55], particularly among people living with HIV without access to antiretroviral therapy (ART) and insu cient or late ART receipt [56].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%